Sports Technology Research at Technical University of Munich, Germany - Senner, V. (5. Asia-Pacific Congress on Sport Technology 2011 Melbourne, 2011)
Information on projects abaout Fatique (Improvement of existing calculation models) - Impact (load levels effects of damage on residual strength and fatigue behaviour, developement of design guidelines for impact tolerant constructions - Non destructive Inspection